2018
DOI: 10.2147/vhrm.s165960
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of peripheral artery disease in black Africans with HIV infection: a cross-sectional hospital-based study

Abstract: BackgroundThe prevalence of peripheral artery disease (PAD) is not well known among HIV-infected patients in Africa. The aim of this study was to determine the prevalence and associated risk factors of PAD among HIV-infected patients at the Douala General Hospital (DGH).MethodsThis was a cross-sectional descriptive and analytic study between November 2015 and April 2016. We recruited patients aged ≥21 years, diagnosed with HIV infection, and who were receiving care at the DGH. We collected sociodemographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
13
1
2
Order By: Relevance
“…The prevalence of LEAD in the general population has been estimated between 2 and 4% in two large studies in young adults in USA 24 , 25 . In a cross-sectional hospital-based study in black Africans, the LEAD prevalence was estimated at 6.9% 14 . A recent Nigerian study reported no difference of LEAD prevalence between virologically-suppressed individuals and controls 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of LEAD in the general population has been estimated between 2 and 4% in two large studies in young adults in USA 24 , 25 . In a cross-sectional hospital-based study in black Africans, the LEAD prevalence was estimated at 6.9% 14 . A recent Nigerian study reported no difference of LEAD prevalence between virologically-suppressed individuals and controls 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This association has also been described, in hospital Spanish and Cameroon populations. These studies had either important LEAD diagnosis bias 14 or exclusively focused on asymptomatic LEAD subjects 17 . Our results accurately analysed the association between HIV clinical stage and LEAD in urban and rural HIV outpatients and indicate that the severity of HIV infection could influence the arteries injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV is fast gaining reputation as a leading cause of CVDs in sub-Saharan Africa (SSA) [ 3 , 4 ]. In addition to the usual risk factors for CVDs in the general populations, People Living with HIV (PLHIV) may have addition risk factors related to endothelial dysfunction, metabolic effects of antiretroviral drugs such as dyslipidemias, insulin resistance and the chronic inflammation induced by Human Immunodeficiency Virus (HIV) which heighten their predisposition to CVDs [ 5 , 6 ]. The burden of HIV remains high in SSA and Nigeria is among the countries with the highest prevalence with about 3.5 million people infected [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It involves a complex pathophysiologic process resulting in deposition of fatty materials, thickening of the intima and narrowing of blood vessels. The combination of endothelial dysfunction, chronic inflammation and dyslipidemias are central to the pathogenesis of atherosclerosis and these conditions have been documented in HIV-infected patients [ 5 , 6 , 9 ]. The presence of subclinical atherosclerosis (SCA) which can be assessed by carotid intimal media thickness (CIMT) is a harbinger for CVDs [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%